Product Market Competition, Productivity, and Jobs : The Case of South Africa - Dauda, Seidu (World Bank, Washington, DC, 2019)
The degree of concentration and market power in South African markets has been the topic of much policy discussion. However, there has been little evidence on what drives market power and the impact of the degree of competition in South African markets on economic outcomes. This paper improves on previous markup estimates for South Africa using a methodology developed by De Loecker and Warzynski (2012) applied to tax administrative data for 2010–14. The paper then explores the firm-level determinants of the estimated markups and assesses the link between competition and firm-level outcomes, including productivity, employment, and wages. The analysis finds that average markups across the economy appear to have risen between 2010 and 2014. Larger firms, higher-intensity exporters, and firms with greater sales shares charge higher markups than comparator firms in South Africa, even after controlling for efficiency. Moreover, lower product market competition has a significant, negative effect on productivity growth, employment growth, and wage growth in South African manufacturing industries. Higher sales-weighted and value-added-weighted average industry-level markups are associated with lower industry-level entry rates. The findings highlight the importance of implementing sound pro-competition government interventions and the significant economic benefits associated with such policies.